Physicochemical Characteristics of Pregelatinized Banana Flour with Variations in Cooking Temperature - Nelly D Pesireron; Priscilia Picauly; Syane Palijama (Jurnal Agrosilvopasture-Tech, 2022)
The objective of this study was to determine, based on the physicochemical features of pregelatinized flour, the optimal cooking temperature for its production. This study employed a completely random design with four levels of cooking temperature: 75 °C, 80°Ce, 85° C, and 90° C, with two replications. The moisture content, ash content, water absorption, and bulk density of Tongka Langit banana flour (control) and pregelatinization were observed. Tongka Langit banana flour exhibited the following characteristics: moisture content (7.35–9.65%), ash content (3.42–3.75%), water absorption (1.76–3.38%), and bulk density (1.63g/mL–2.03). This study concluded that Tongka Langit banana flour treated with the pregelatinization process can improve its physicochemical properties.